2014
DOI: 10.1002/jccs.201400065
|View full text |Cite
|
Sign up to set email alerts
|

A Green Approach to the Synthesis of Pd‐Ni/Graphene via Electrochemical Exfoliation of Graphite from Used Battery for the Electrocatalysis of Ethanol

Abstract: A simple, environmentally benign, and cost‐effective approach is described to prepare graphene via electrochemical exfoliation of graphite rod from spent batteries. PdNi was deposited on electrochemically exfoliated graphene materials with the electrocatalyst synthesized using a borohydride‐facilitated reduction. Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM) analysis confirmed the exfoliation of graphite from used batteries and deposition of PdNi on electrochemically exfoliated grapheneb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The Pd nanoparticles can further be analyzed in the TEM images shown in Figure 2c−f, where the average diameter of the Pd nanoparticles was found to be 5.8 ± 1.8 nm for both carbon and rGO supported catalyst, which is comparable in size to Pd supported on rGO reported elsewhere. 20,57 However, the average particle size from the XRD data (4.3 nm) is smaller than this value but is within the standard deviation. The lattice fringes can be seen in Figure S2c,d corresponding to the fcc facets of Pd with a dspacing of approximately 0.23 nm, which corroborates with the obtained XRD data.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…The Pd nanoparticles can further be analyzed in the TEM images shown in Figure 2c−f, where the average diameter of the Pd nanoparticles was found to be 5.8 ± 1.8 nm for both carbon and rGO supported catalyst, which is comparable in size to Pd supported on rGO reported elsewhere. 20,57 However, the average particle size from the XRD data (4.3 nm) is smaller than this value but is within the standard deviation. The lattice fringes can be seen in Figure S2c,d corresponding to the fcc facets of Pd with a dspacing of approximately 0.23 nm, which corroborates with the obtained XRD data.…”
Section: ■ Results and Discussionmentioning
confidence: 67%
“…The electrochemically exfoliated graphene (EGO) material was washed and filtered using 0.45 m membrane filter to remove the DMF. The EGO was dispersed in water and was freeze-dried to obtain powdered EGO [10].…”
Section: Preparation Of Graphene Via Electrochemical Exfoliationmentioning
confidence: 99%
“…Aside from adding promoters to improve catalytic activity, the catalyst can be deposited on a support material with large surface area such as carbon-based materials [8,9]. Studies have shown that Pd catalyst supported by graphene gave enhanced catalytic activity [10,11]. Graphene can improve the performance of the catalyst by providing deposition sites for the (electro)chemical reduction of the catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have studied mono-metallic and binary electrocatalyst with graphene as support but few have done so with ternary electrocatalysts. Recently, we have synthesized PdNi supported on electrochemically exfoliated graphene oxide [17]. The synthesized catalyst composite gave a higher electrocatalytic performance compared to PdNi supported on carbon black.…”
Section: Introductionmentioning
confidence: 99%